2010
DOI: 10.1111/j.1095-8312.2010.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromones and trail-following pheromone in the basal termites Zootermopsis nevadensis (Hagen) and Z. angusticollis (Hagen) (Isoptera: Termopsidae: Termopsinae)

Abstract: In the context of an evolutionary study of the chemical communication in termites, sex pheromones and trail-following pheromones were investigated in two Termopsidae, Zootermopsis nevadensis and Z. angusticollis. In these species, in which the presence of sex-specific pheromones has been demonstrated previously, the chemical structure of the female sex pheromone has now been identified as (5E)-2,6,10-trimethylundeca-5,9-dienal and the male sex pheromone as (+)-or (-)-syn-4,6-dimethyldodecanal. The amount of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…While this appears to be true in some species (e.g., Peppuy et al 2004;, in others only pheromone quantities differ between congenerics (Bordereau et al 1993(Bordereau et al , 2010Connétable et al 2012). As a result, reproductive isolation is probably maintained by other mechanisms, such as the differential timing of the dispersal and contact species recognition cues (Connétable et al 2012), which are further discussed below.…”
Section: Mate Attraction and Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this appears to be true in some species (e.g., Peppuy et al 2004;, in others only pheromone quantities differ between congenerics (Bordereau et al 1993(Bordereau et al , 2010Connétable et al 2012). As a result, reproductive isolation is probably maintained by other mechanisms, such as the differential timing of the dispersal and contact species recognition cues (Connétable et al 2012), which are further discussed below.…”
Section: Mate Attraction and Recognitionmentioning
confidence: 99%
“…However, these termites nonetheless have active sternal glands and successfully follow artificial trails (Sillam-Dussès et al 2009b;Bordereau et al 2010), which suggests that they may be using trails to orient themselves within the network of galleries located in the wood they inhabit. Trail-following behavior is sometimes considered to have originated from the recruitment associated with specific alarms, during which trail-following pheromone is used to guide the recruited nestmates to the disturbance site.…”
Section: Foraging and Food Markingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, both trail and sex pheromones most often consist of a single compound, not blends of compounds as in numerous other insects. However, some recent studies demonstrated the presence of minor components in addition to these major compounds (Sillam-Dussès et al, 2009Bordereau et al, 2010;Anani Kotoklo et al, 2010), suggesting that minor active components could have been overlooked in the past.…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for (3Z,6Z)-dodeca-3,6-dien-1-ol in Ancistrotermes pakistanicus and probably also for the diterpene neocembrene-A in Nasutitermes and Trinervitermes (Birch et al, 1972;McDowell and Oloo, 1984;Hall and Traniello, 1985). n-Tetradecyl propionate elicits attraction in Reticulitermes flavipes when offered to males in unnaturally high concentrations (Clément et al, 1989), and recently (E)-2,6,10-trimethylundeca-5,9-dienal was identified as female sex pheromone in Zootermopsis species (Bordereau et al, 2006). Among the contact gustatory stimuli, trilinolein was described as a specific compound for female tergal glands in Coptotermes formosanus (Bland et al, 2004).…”
Section: Introductionmentioning
confidence: 99%